2009
DOI: 10.1111/j.1365-2958.2009.06653.x
|View full text |Cite
|
Sign up to set email alerts
|

Stringent response in Vibrio cholerae: genetic analysis of spoT gene function and identification of a novel (p)ppGpp synthetase gene

Abstract: SummaryRelA and SpoT of Gram-negative organisms critically regulate cellular levels of (p)ppGpp. Here, we have dissected the spoT gene function of the cholera pathogen Vibrio cholerae by extensive genetic analysis. Unlike Escherichia coli, V. cholerae DrelA DspoT cells accumulated (p)ppGpp upon fatty acid or glucose starvation. The result strongly suggests RelA-SpoT-independent (p)ppGpp synthesis in V. cholerae. By repeated subculturing of a V. cholerae DrelA DspoT mutant, a suppressor strain with (p)ppGpp 0 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 41 publications
(105 reference statements)
1
105
0
2
Order By: Relevance
“…This phenotype is due to an additional ppGpp synthase in V. cholerae, RelV (19). The level of ppGpp accumulation was higher in the ⌬relA ⌬spoT double mutant when compared with that in wild type N16961 (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This phenotype is due to an additional ppGpp synthase in V. cholerae, RelV (19). The level of ppGpp accumulation was higher in the ⌬relA ⌬spoT double mutant when compared with that in wild type N16961 (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In Gram-negative bacteria, the intracellular level of ppGpp is modulated by RelA (monofunctional synthetase) and SpoT (bifunctional synthetase-hydrolase) (18). Apart from the relA and spoT genes, the novel gene relV has been identified in V. cholerae, the product of which has been shown to be involved in ppGpp synthesis under glucose or fatty acid starvation in a ⌬relA ⌬spoT double mutant (19). CgtA, the conserved bacterial GTP-binding protein, is an essential protein and has been shown to interact with SpoT in V. cholerae and Escherichia coli.…”
mentioning
confidence: 99%
“…The identification of these small (p)ppGpp synthetase enzymes in Gram-positive bacteria reinvigorated the scientific interest in this fundamental stress response pathway. As a result, recent bioinformatic and genetic analysis indicated that single-domain (p)ppGpp-synthesizing and -hydrolysing enzymes can be found, alone or in combination, in a number of organisms, including archaea, bacteria, plants and animals (Atkinson et al, 2011;Das et al, 2009;Sun et al, 2010).…”
Section: S Mutans Is the Bacterial Paradigm Of Lactic Acid Bacteria mentioning
confidence: 99%
“…On the other hand their C-terminally located conserved domains TGS (this domain is conserved in threonyl t-RNA synthetase, GTPases and SpoT proteins) and ACT (this domain is conserved in acetolactate synthase, chorismate mutase and TyrR receptor proteins) (Aravind & Koonin, 1998;Atkinson et al, 2011;Potrykus & Cashel, 2008), are involved in regulation of enzymic activities (Battesti & Bouveret, 2006;Das et al, 2009;Gropp et al, 2001;Mechold et al, 2002;Schreiber et al, 1991). In SpoT/Rel enzymes, the hydrolase domain carries highly conserved histidine-aspartic acid (HD) residues (Aravind & Koonin, 1998;Das et al, 2009;Potrykus & Cashel, 2008). However, in RelA, the HD residues are substituted with other amino acids leading to impaired (p)ppGpp hydrolase activity function (Aravind & Koonin, 1998).…”
Section: Introductionmentioning
confidence: 99%